Nurse in patients' health status assessment: Data from a pilot study assessing agreement among nurse and gastroenterologist in computing IBD-clinical scores. Issue 10 (October 2017) - Mocciaro, Filippo; Pecoraro, Giulia Maria; Di Mitri, Roberto; Scimeca, Daniela; Bossa, Fabrizio; Russo, Giuseppina; Martino, Giuseppina; Costanza, Vincenzo; Profita, Maria Antonella; Orlando, Concetta; Profeta, Gianfranco; Tinè, Fabio
Abstract: Introduction: Crohn's Disease (CD) and Ulcerative Colitis (UC) are chronic, systemic Inflammatory Bowel Diseases (IBDs) that need a multidisciplinary approach involving not only different medical specialists but also qualified nurses. Aim: We evaluated the concordance between IBD-nurse and physician in computing Clinical Activity Scores in IBD-patients treated with biologics. Methods: We enrolled all consecutive IBD-patients treated with biologics in two referral centers for IBD-care. For each patient, a gastroenterologist and a nurse blindly filled-out a form to assess the Harvey–Bradshaw Index (HBI) in CD or the partial MAYO score in UC. All data were recorded to assess the beyond chance agreement (concordance) using the k statistic. Results: 87 patients were enrolled. The agreement in all patients by k value was substantial (66%), ranging from moderate to substantial (95% CI from 51% to 80%). The main reason of disagreement was about the scoring of remission versus mild activity, and that of mild versus moderate activity, both in CD and UC. For the HBI, the best agreement was for well-being on the previous day (k 62%) and the least one for abdominal mass (k 35%). Conclusions: Our study shows an acceptable strength of agreement among nurse and gastroenterologist in evaluating the disease activity of IBD-patients through the calculation of clinical scores.